Functional Analysis of Direct In Vitro Effect of Phosphorylated Tau on Mitochondrial Respiration and Hydrogen Peroxide Production - Fišar, Zdeněk; Hroudová, Jana (Biomolecules, 2025)
The neurotoxicity of phosphorylated tau protein (P-tau) and mitochondrial dysfunction play a significant role in the pathophysiology of Alzheimer's disease (AD). In vitro studies of the effects of P-tau oligomers on mitochondrial bioenergetics and reactive oxygen species production will allow us to evaluate the direct influence of P-tau on mitochondrial function. We measured the in vitro effect of P-tau oligomers on oxygen consumption and hydrogen peroxide production in isolated brain mitochondria. An appropriate combination of specific substrates and inhibitors of the phosphorylation pathway enabled the measurement and functional analysis of the effect of P-tau on mitochondrial respiration in defined coupling control states achieved in complex I-, II-, and I&II-linked electron transfer pathways. At submicromolar P-tau concentrations, we found no significant effect of P-tau on either mitochondrial respiration or hydrogen peroxide production in different respiratory states. The titration of P-tau showed a nonsignificant dose-dependent decrease in hydrogen peroxide production for complex I- and I&II-linked pathways. An insignificant in vitro effect of P-tau oligomers on both mitochondrial respiration and hydrogen peroxide production indicates that P-tau-induced mitochondrial dysfunction in AD is not due to direct effects of P-tau on the efficiency of the electron transport chain and on the production of reactive oxygen species.
Keywords: proteiny tau; Mitochondria; phosphorylated tau; Alzheimer’s disease; reaktivní formy kyslíku; Cell Respiration; Brain; fosforylace; buněčné dýchání; Phosphorylation; respiratory state; peroxid vodíku; transport elektronů; Hydrogen Peroxide; isolated mitochondria; tau Proteins; hydrogen peroxide; krysa rodu Rattus; spotřeba kyslíku; Reactive Oxygen Species; Electron Transport; Oxygen Consumption; Animals; lidé; mitochondrial dysfunction; Humans; zvířata; Rats; mozek; mitochondrie